Substratum-dependent moss microhabitat types alter soil nematode community structure in the mixed coniferous forest of Dachigam National Park, Jammu and Kashmir - Humira Nesar (Elsevier, 2021)
Mosses although lack a proper rhizosphere, and poorly exploit the substratum on which they grow, still play complex role in ecological processes by providing nutrients and shelter to various organisms. Among the moss fauna, nematodes are the most abundant inhabitants. Keeping this in mind, the present study investigates how nematode communities differ among substratum-dependent moss microhabitats from forest soil. For this, samples were collected from five different microhabitats (FS: forest soil, MS: mosses on soil, MR; mosses on rocks, MLT: mosses on lower tree trunk and MUT: mosses on upper part of tree trunk), from the mixed coniferous forest of Dachigam National Park, Srinagar, Jammu & Kashmir. Results showed that the distribution pattern of nematode assemblages mirror the variation of microclimate. Total nematode abundance, trophic abundance (bacterivores, fungivores, herbivores, predators) and diversity (Shannon index, Simpson index) were highest in FS and lowest in MUT. Maturity index indicated more stable nematode communities in forest soil compared to different moss microhabitats. Results from NMDS showed clear separation of samples between microhabitats forming isolated clusters. Enrichment index depicted more enriched condition in MUT and least in FS. In general, our findings provide insights that more abundant, diverse and stable nematode communities are supported in undisturbed forest soil compared to desiccation-prone moss microhabitats.